NK Cells in the Tumor Microenvironment as New Potential Players Mediating Chemotherapy Effects in Metastatic Melanoma - Garofalo, Cinzia; De Marco, Carmela; Cristiani, Costanza Maria (Frontiers in Oncology, 2021)
Until the last decade, chemotherapy was the standard treatment for metastatic cutaneous melanoma, even with poor results. The introduction of immune checkpoints inhibitors (ICIs) radically changed the outcome, increasing 5-year survival from 5% to 60%. However, there is still a large portion of unresponsive patients that would need further therapies. Several evidences showed that chemotherapy also possesses immunomodulatory properties, suggesting that the combination with ICIs might represent a valuable therapeutic strategy. In this review, we will discuss the anti-cancer immunological effects mediated within the tumor microenvironment (TME) by the standard chemotherapeutics used in metastatic melanoma, with a specific focus on the Natural Killer (NK) cell-mediated mechanisms. NK cells are skin-resident innate cytotoxic lymphocytes that recognize and kill virus-infected as well as cancer cells thanks to a balance between inhibitory and activating signals delivered by surface molecules expressed by the target. Since NK cells are equipped with cytotoxic machinery but lack of antigen restriction and needing to be primed, they represent a prompt barrier against tumor growth and spread. Alongside traditional systemic melanoma chemotherapy, a new pharmacological strategy based on nanocarriers loaded with chemotherapeutics is developing. The use of nanotechnologies represents a very promising approach to improve drug tolerability and effectiveness thanks to the targeted delivery of the therapeutic molecules. Here, we will also discuss the recent developments in using nanocarriers to deliver anti-cancer drugs within the melanoma microenvironment in order to improve chemotherapeutics effects.